Comparative genomics and metabolomics reveal phytohormone production, nutrient acquisition, and osmotic stress tolerance in Azotobacter chroococcum W5 - Elakkya, M.; González-Salazar, Luz A.; López-Reyes, Karina; Rebelo-Romão, Inês; Sousa, André; Gödde, Victoria; Niehaus, Karsten; Thenappan, Dhivya P.; Vilchez, Juan Ignacio; Paul, Sangeeta; Licona-Cassani, Cuauhtemoc (Frontiers in Microbiology, 2025)
IntroductionConcerns about ecological degradation and reduced biodiversity have intensified the search for sustainable solutions in agriculture. The use of plant growth-promoting bacteria (PGPB) offers a promising alternative to enhance soil quality and crop yield while reducing the consumption of chemical fertilizers.MethodsHere, we characterize the plant growth-promoting potential of Azotobacter chroococcum W5 through comparative genomics, in vitro experiments, and metabolomic analyses.ResultsComparative genomic analysis revealed plant growth-promoting traits, including phytohormone biosynthesis, nutrient acquisition, stress adaptation, and colonization in the A. chroococcum W5 strain. Experimental assays confirmed the production of auxin, gibberellic acid, phosphate solubilization, moderate nitrogen fixation, and growth on ACC. Wheat seed inoculation significantly enhanced germination metrics, seedling vigor, and altered carbohydrate metabolism in the seed endosperm. Under salt and osmotic stress, A. chroococcum W5 metabolomic profiling revealed adaptive responses, including elevated levels of osmoprotectants (proline, glycerol) and oxidative stress markers such as 2-hydroxyglutarate, while putrescine and glycine decreased.DiscussionOur results show that the A. chroococcum W5 strain has great potential for the development of novel formulations. More importantly, our results highlight the potential of using plant growth-promoting microorganisms for innovative, sustainable solutions in agriculture.